2021
DOI: 10.1111/anu.13337
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lipid levels affect growth, feed utilization, lipid deposition, health status and digestive enzyme activities of juvenile Siberian sturgeon, Acipenser baerii

Abstract: A 10-week experiment was conducted to evaluate the effects of dietary lipid levels on growth, feed utilization, lipid deposition, health status and digestive enzyme activities of juvenile Siberian sturgeon (Acipenser baerii). Six isonitrogenous diets were formulated with lipid levels at 51.1 (L5), 88.7 (L9), 129.6 (L13), 169.3 (L17), 208.4 (L21) and 248.8 g/kg (L25). The sturgeons fed with L17 had the highest growth and feed utilization. Higher dietary lipid obtained significantly lower PPV than that of L17 (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…The positive correlation between serum TG content and dietary lipid contents suggested that the Yangtze sturgeon showed higher lipase activity and more active endogenous lipid kinetics in response to high‐lipid diets. The results agree well with the findings on other sturgeon species (Guo et al, 2011; Ren et al, 2021). In addition, serum biochemical parameters can intuitively reflect the health and metabolic state of the body.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The positive correlation between serum TG content and dietary lipid contents suggested that the Yangtze sturgeon showed higher lipase activity and more active endogenous lipid kinetics in response to high‐lipid diets. The results agree well with the findings on other sturgeon species (Guo et al, 2011; Ren et al, 2021). In addition, serum biochemical parameters can intuitively reflect the health and metabolic state of the body.…”
Section: Discussionsupporting
confidence: 92%
“…Guo et al (2011) reported that the dietary lipid requirement for juvenile hybrid sturgeon (~66.7 g) ( Acipenser baerii ♀ × Acipenser gueldenstaedtii ♂) was estimated to be 11.1% as evaluated by growth performance. The optimal lipid requirements for juvenile Siberian sturgeon ( A. baerii ) (14.19 g) (Ren et al, 2021) and American paddlefish ( Polyodon spathula) (81.38 g) (Liu et al, 2018) were reported to be 169.9–176.0 and 78.8–96.9 g/kg, respectively, suggesting that different sturgeon species had varied lipid requirements. In addition, it has been demonstrated that the nutrient requirements of fish were affected by multiple factors including age/size, feed ingredients, rearing environments, and so on.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insufficient or excess dietary lipid levels elevated the ALT and AST values in golden pompano [ 72 ]. This showed liver dysfunction in Siberian sturgeon ( Acipenser baerii ) [ 73 ] and hybrid snakehead ( Channa argus× Channa maculata ) [ 74 ]. The 2Stresses group had lower ALT levels than the other treatments, indicating that this group had slightly greater liver health, which is consistent with improved growth and immunological response.…”
Section: Resultsmentioning
confidence: 99%